A neutralizing recombinant single chain antibody, scFv, against BaP1, A P-I hemorrhagic metalloproteinase from Bothrops asper snake venom - Castro, J. M. A. (2014)
BaP1 is a P-I class snake venom metalloproteinase (SVMP) relevant in the local tissue damage associated with envenomings by Bothrops asper, a medically important snake species in Central America and parts of South and North America. The main treatment for these accidents is the passive immunotherapy using antibodies raised in horses. In order to obtain more specific and batch-to-batch consistent antivenons, recombinant antibodies are considered a good option compared to animal immunization. We constructed a recombinant single chain variable fragment (scFv) from a monoclonal antibody against BaP1 (MABaP1) formerly secreted by a hybridoma clone. This recombinant antibody was cloned into pMST3 vector in fusion with SUMO protein and contains VH and VL domains linked by a flexible (G4S)3 polypeptide (scFvBaP1). The aim of this work was to produce scFvBaP1 and to evaluate its potential concerning the neutralization of biologically important activities of BaP1. The cytoplasmic expression of this construct was successfully achieved in C43 (DE3) bacteria. Our results showed that scFvBaP1-SUMO fusion protein presented an electrophoretic band of around 43 kDa from which SUMO alone corresponded to 13.6 kDa, and only the scFv was able to recognize BaP1 as well as the whole venom by ELISA. In contrast, neither an irrelevant scFv anti-LDL nor its MoAb partner recognized it. BaP1-induced fibrinolysis was significantly neutralized by scFvBaP1, but not by SUMO, in a concentration-dependent manner. In addition, scFvBaP1, as well as MaBaP1, completely neutralized in vivo hemorrhage, muscle necrosis, and inflammation induced by the toxin. Docking analyses revealed possible modes of interaction of the recombinant antibody with BaP1. Our data showed that scFv recognized BaP1 and whole B. asper venom, and neutralized biological effects of this SVMP. This scFv antibody can be used for understanding the molecular mechanisms of neutralization of SVMPs, and for exploring the potential of recombinant antibody fragments for improving the neutralization of local tissue damage in snakebite envenoming.